Dynamic response of porous functionally graded sandwich nanoplates using nonlocal higher-order isogeometric analysis. (15th June 2022) - Pham, Quoc-Hoa; Nguyen, Phu-Cuong; Thanh Tran, Trung
Highlights: Dynamic response of PFG sandwich nanoplates is successfully developed using isogeometric analysis. Isogeometric analysis employs the higher-order shear deformation theory with different continuous functions. The obtained results show the accuracy and fast convergence compared to other methods even with the coarse mesh. The PFG core layer positively affects on the free and forced vibrations of sandwich nanoplates. The effects of geometrical parameters and material properties are investigated in detail. Abstract: The main goal of this work is to indicate the dynamic response of sandwich nanoplates with a porous functionally graded (PFG) core using isogeometric analysis (IGA) based on the higher-order shear deformation theory (HSDT) with different continuous functions f ( z ) . The small-scale effect appearing in nanostructures is included by employing the nonlocal elasticity theory. The sandwich nanoplate consists of three layers: the metal bottom layer, the ceramic top layer, and the core layer being PFG materials with the log-uneven porosity distribution. The convergence and reliability of the proposed method are verified by comparing obtained numerical results to those of other published works. Moreover, some examples are conducted to examine the impact of parameters on the dynamic response of sandwich nanoplates with the PFG core.